The Netherbow Port (Proceedings of the Society of Antiquaries of Scotland, 1912)
The Netherbow was an important boundary throughout the Middle Ages. Above was the ancient town of Edinburgh; below, the Canongate, under the jurisdiction of the Abbot of Holyrood and his bailies. The position of this gate was originally fixed by the line of the ancient fortified wall of the town, traces of which still exist. Many events connected with the history of Edinburgh occurred at the Netherbow and these are recounted. Great works were carried out at the Netherbow in 1571 for purposes of defence, and a substantial portion of this extensive gateway was most likely erected in that year, but part must be earlier than that date, and probably belongs to the prosperous and peaceful reign of James V.